The impact of merger legislation on bank mergers - Elena Carletti; Steven Ongena; Jan-Peter Siedlarek; Giancarlo Spagnolo (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2015)
We study the impact on bank merger activity of the strengthening in merger control legislation introduced in Europe between 1989 and 2004. We find that strengthening merger control increases the abnormal returns on bank target stocks in the days around the merger announcement by 7 percentage points relative to before the new legislation. We discuss several potential explanations for this effect of the change in legislation by studying changes in merger characteristics. We find a weak increase in the pre-merger profitability of target banks, a decrease in the size of acquirers and a decrease in the share of transactions in which banks are acquired by other banks. Other merger properties, including the size and risk profile of targets, the geographic overlap of merging banks and the stock market response of rival banks in the country appear unaffected. The evidence is consistent with legislation changes leading to transactions being undertaken that are more profitable and more pro-competitive.
Keywords: 330